Penelaahan Alkitab sebagai Prediktor Pertumbuhan Iman Siswa Kristen di SMKN 2 Tapung Hilir Kabupaten Kampar - Lena Anita Sulastri Purba; Afriani Manalu; Herlina Sonia Sinaga (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
This study examines the effect of Bible study on the faith growth of Christian students at SMKN 2 Tapung Hilir, Kampar Regency. Using a quantitative survey approach, data were collected from 22 Christian students selected through total sampling. Valid and reliable questionnaires were analyzed using simple linear regression with SPSS. The results show that Bible study has a positive and significant effect on students’ faith growth. The correlation coefficient indicates a very strong relationship (r = 0.827, p < 0.05), while the coefficient of determination (R² = 0.684) shows that Bible study explains 68.4% of the variance in faith growth, with the remaining 31.6% influenced by other factors. These findings demonstrate that Bible study plays an important role in fostering students’ faith growth and should be systematically integrated into Christian Religious Education and spiritual formation programs. The findings also indicate that regular participation in Bible study encourages students to strengthen their understanding of biblical teachings, develop positive Christian values, and apply their faith in daily life. Therefore, schools are encouraged to provide consistent and structured Bible study activities to support students’ spiritual development and strengthen their Christian character within the educational environment.